DESIGN AND DEVELOPMENT OF CONTROLLED POROSITY OSMOTIC TABLETS OF GARCINIA INDICA EXTRACT - Jagtap, Prajakta Chandrakant; Prakya, Vijayalakshmi; Bhise, Kiran Sanjay (Journal of Drug Delivery and Therapeutics, 2018)
The present study deals with the development and evaluation of controlled porosity osmotic pump (CPOP) tablets containing inclusion complexes of ethanolic extract of Garcinia indica fruit rind. Wet granulation method was used for the development of core tablets. Core tablets were incorporated with different concentrations of sodium chloride as osmogen and additives. The CPOP tablets were coated with cellulose acetate as a wall forming material and HPMC acts as pore forming material in SPM. The formulated tablets were evaluated for FTIR, DSC, pre-compression parameters, post compression parameters, in vitro drug release study and scanning electron microscopy study. The optimized formulation had no significant effect on the pH and agitation intensity. SEM images revealed that no pores were found before dissolution and after dissolution had shown the porous nature of the membrane. It was found that the optimized formulation (P4) delivers a drug at a zero-order rate for 24 hours. Short term stability study at 40±2ºC /75±5% RH for the months on the optimized formulation indicated that there was no significant change in weight variation, % friability, drug content and in vitro drug release. Keywords: Osmotic system, cellulose acetate, pore former, controlled porosity, Garcinia indica